Nitrogen and cultivars as field strategies to improve the nutritional status of wheat grain and flour. (November 2021) - Reznick, João Paulo Kruger; Barth, Gabriel; Kaschuk, Glaciela; Pauletti, Volnei
Abstract: Wheat grows better and accumulates more nutrients in its grains when fertilized with N. However, improvements in grain quality and flour could be affected during the milling process and by differences in the edaphoclimatic conditions where the crop is grown. Field experiments were performed in Ponta Grossa-Paraná and Itaberá-São Paulo, Brazil, during 2015, under a randomized complete block system, with three replicates and a factorial design, with five cultivars (BRS Gralha Azul, TBIO Sinuelo, TBIO Toruk, CD 1104 and ORS Vintecinto) and six rates of N fertilization (0, 40, 80, 120, 160, and 200 kg N ha −1 ) as the factors. The N fertilization increased wheat yield (from 1315 to 3017 kg ha −1 ) and grain protein content (from 158 to 173 kg ha −1 ) in Ponta Grossa, but not in Itaberá (average grain yield of 4024 kg ha −1 ). The N fertilization increased the flour protein content in the two locations and the Zn content in the grains and in the flour in Itaberá, but not in Ponta Grossa. Wheat cultivars presented variable concentrations of nutrients in the grains and flour, and the nutrient status in the grains was correlated with that in the flour. In conclusion, both N fertilization and cultivar selection were effective strategies to increase the quality of wheat flour but the magnitude of the improvements were affected by edaphoclimatic conditions. Graphical abstract: Image 1 Highlights: N fertilization increases wheat protein and yield. N fertilization increases the nutrients in the wheat flour differently in distinct edaphoclimatic conditions. N fertilization may contribute to increase Zn contents in the wheat flour. Cultivar is a suitable strategy to improve elemental nutrient status of wheat flour. It is possible to select cultivars for more nutrients in the flour by analysing the grains.